2009
DOI: 10.1016/j.engfracmech.2009.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Fracture simulation of CFRP laminates in mixed mode bending

Abstract: This paper analyses the progressive mixed mode delamination failure in unidirectional and multidirectional composite laminates using fracture experiments, finite element (FE) simulations and an analytical solution. The numerical model of the laminate is described as an assembly of damageable layers and bilinear interface elements subjected to mixed mode bending. The analytical approach is used to estimate the total mixed mode and decomposed fracture energies for laminates with different stacking sequences, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 43 publications
2
35
0
1
Order By: Relevance
“…Nevertheless, the shear cusps in the MMF specimen were less significant and more random compared to the ENF specimen, which was similar to the observation by Naghipour et al [6]. In addition, the roughness of the MMF specimen was less than the ENF specimen [7].…”
Section: Failure Analysis and Prevention 42supporting
confidence: 78%
See 2 more Smart Citations
“…Nevertheless, the shear cusps in the MMF specimen were less significant and more random compared to the ENF specimen, which was similar to the observation by Naghipour et al [6]. In addition, the roughness of the MMF specimen was less than the ENF specimen [7].…”
Section: Failure Analysis and Prevention 42supporting
confidence: 78%
“…However, significant shear cusps were observed on the 0 l a y e ri nt h e4 5 direction, which was attributed to the shear mode loading. It has also been reported that the high shear mode would draw large shear cusps [6,7]. A certain amount of matrix cracking was observed on the 45 layer, which was believed to be due to the interaction between 0 and 45 layers during shearing.…”
Section: Failure Analysis and Prevention 42mentioning
confidence: 99%
See 1 more Smart Citation
“…Adhesive layers between the fibre layers were modelled using the eight-node threedimensional cohesive elements COHD8. Cohesive elements are generally capable of simulating damage and delamination in composites (Naghipour et al 2009;Shi et al 2012;Al-Zubaidy et al 2013). A triangular traction-separation cohesive law with linear softening is used to characterize the material behaviour of the adhesive.The CFRP patches are meshed with an 8-node quadrilateral in-plane general-purpose continuum shell, reduced integration with hourglass control, finite membrane strains (SC8R).…”
Section: Element Types and Modelmentioning
confidence: 99%
“…Since cohesive elements represent zeroor infinitesimal-thickness interfaces, high stiffness is required to model the connections. Therefore, the interface stiffness should be large enough to avoid relative displacements between the connected ply elements but also not too large to cause numerical problems such as spurious oscillations in interfacial traction of the cohesive element [11,12,27]. This stiffness is usually calibrated by numerical 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 12 simulations as it cannot be measured directly through the experiments.…”
Section: Stiffness Of Cohesive-zone Elementsmentioning
confidence: 99%